Ginsenoside Rd Attenuates Mitochondrial Permeability Transition and Cytochrome c Release in Isolated Spinal Cord Mitochondria: Involvement of Kinase-Mediated Pathways - Zhou, Jin-Song (MDPI, 2014)
Ginsenoside Rd (Rd), one of the main active ingredients in Panax ginseng, has multifunctional activity via different mechanisms and neuroprotective effects that are exerted probably via its antioxidant or free radical scavenger action. However, the effects of Rd on spinal cord mitochondrial dysfunction and underlying mechanisms are still obscure. In this study, we sought to investigate the in vitro effects of Rd on mitochondrial integrity and redox balance in isolated spinal cord mitochondria. We verified that Ca(2+) dissipated the membrane potential, provoked mitochondrial swelling and decreased NAD(P)H matrix content, which were all attenuated by Rd pretreatment in a dose-dependent manner. In contrast, Rd was not able to inhibit Ca(2+) induced mitochondrial hydrogen peroxide generation. The results of Western blot showed that Rd significantly increased the expression of p-Akt and p-ERK, but had no effects on phosphorylation of PKC and p38. In addition, Rd treatment significantly attenuated Ca(2+) induced cytochrome c release, which was partly reversed by antagonists of Akt and ERK, but not p-38 inhibitor. The effects of bisindolylmaleimide, a PKC inhibitor, on Rd-induced inhibition of cytochrome c release seem to be at the level of its own detrimental activity on mitochondrial function. Furthermore, we also found that pretreatment with Rd in vivo (10 and 50 mg/kg) protected spinal cord mitochondria against Ca(2+) induced mitochondrial membrane potential dissipation and cytochrome c release. It is concluded that Rd regulate mitochondrial permeability transition pore formation and cytochrome c release through protein kinases dependent mechanism involving activation of intramitochondrial Akt and ERK pathways.